2001
DOI: 10.1039/b007158g
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sampling and analysis methods for low­ppbC levels of volatile organic compounds in ambient air

Abstract: A carefully designed study was conducted during the summer of 1998 to collect samples of ambient air by canisters and compare the analysis results to direct sorbent preconcentration results taken at the time of sample collection. Thirty-two 1 h sample sets were taken, each composed of a "near-real-time" sample analyzed by an autoGC-MS XonTech 930/Varian Saturn 2000 system, and Summa and Silco canisters. Hourly total non-methane organic carbon (TNMOC), ozone, and meteorological measurements were also made. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…The canisters were analyzed 1-7 days after collection with the same concentrator/GC-MS system. 11 They found only slight differences between the near-realtime and canister samples with clear correlations between the two types of samples. Many of the dependent samples had t-test comparisons that were significant.…”
Section: Technical Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The canisters were analyzed 1-7 days after collection with the same concentrator/GC-MS system. 11 They found only slight differences between the near-realtime and canister samples with clear correlations between the two types of samples. Many of the dependent samples had t-test comparisons that were significant.…”
Section: Technical Papermentioning
confidence: 99%
“…Daughtrey et al 11 used two alternative methods to sample CCl 4 , ␣-pinene, isoprene, benzene, n-decane, toluene, m-,p-xylene, and n-octanal in outdoor air. The first method was a near-real-time measurement using a twotrap organic vapor concentrator attached to a gas chromatograph/mass spectrometer.…”
Section: Technical Papermentioning
confidence: 99%
“…Currently this method of determination is the primary procedure utilised to identify VOC's in human breath. Comparative studies have shown however that there is little difference in accuracy of determination even with low concentration (ppbv) organics compared with other detection techniques (15). The study involved the detection of 108 organics in human breath, using both real time and canister analysis.…”
Section: Techniques For Breath Testingmentioning
confidence: 99%
“…Após a análise qualiquantitativa, o espectro resultante pode ser trabalhado para se chegar a um resultado quantitativo. (Tolnai et al, 2000;Doskey & Bialk, 2001;Colon et al, 2001;Ballestra et al, 2001;Mohamed et al, 2002;Ho et al, 2002a;Ho et al,2002b;Daughtrey et al, 2001;Na et al, 2003;Barletta et al, 2002).…”
Section: Determinação Da Composição Elementar Em Bioacumuladores Vegeunclassified